Emotional intelligence and adult attachment: effects on problematic smartphone usage - Aranda López, María; García Domingo, Marta; Fuentes Gutiérrez, Virgina; Linares Martínez, Rocío (Anales de Psicología / Annals of Psychology, 2022)
Smartphone usage can become problematic when individuals have difficulties in emotional regulation. To clarify risk factors for problematic smartphone usage, the study had three objectives: To analyze the effect of emotional intelligence and attachment dimensions on smartphone usage; to evaluate differences by types and styles of attachment in problematic smartphone usage; to explore the roles of sex and age. For this purpose, the Smartphone Dependency and Addiction Scale, the Wong & Law Emotional Intelligence Scale, and the Adult Attachment Questionnaire were used. The study included 552 young adults (M = 21.79, SD = 2.66; 74.1% women) selected by purposive sampling, and classified in Generation Z and Millennials. The results showed that low awareness of one’s emotions (emotional intelligence), poor self-esteem and need for approval, hostile conflict resolution, rancor, and possessiveness (attachment) predicted problematic smartphone usage. Furthermore, insecure type of attachment and negative styles such as fearfulness were closely related to smartphone addiction. Sex had some explanatory power with respect to device use, with women showing higher levels of problematic smartphone usage. In conclusion, the findings support the importance of the secure and positive attachment system, and being able to evaluate and regulate one’s own emotions for preventing problematic smartphone use.